Rodrigo Carazo Odio: His Ideas about Politics, State and Public Companies (Revista Rupturas, 2016)
This article aims to highlight the main ideas of Rodrigo Carazo, former President of the Republic of Costa Rica, concerning politics, the State and public companies. Through the study and interpretation of his work, the article sets out to characterize these concepts from Carazo’s perspective, and thus provide elements to understand some of his decisions. Rodrigo Carazo saw politics as a means to benefit society, which, like the State, must guarantee the fair distribution of resources, while public companies are crucial for development.
Keywords: State; public company; political thought; Rodrigo Carazo